Health care provision and equity - Saman @ Saimy, Intan Syafinaz; Ismail, Noor Haslinda; Esahak, Azreena; Wan, Arinah Deh Sze; Aljaberi, Musheer Abdulwahid; Juni, Muhamad Hanafiah (Community Health Society Malaysia, 2016)
Equity is the absence of avoidable or remediable differences among groups of people that are defined socially, economically, demographically or geographically. It is fundamental to address these determinants in order to achieve equity in health. Health care provision refers to the way inputs such as money, staff, equipment and drugs are combined to deliver health interventions. In the provision of health care for a country, various equity issues has arisen especially with regards to health care services, health care financing, utilization of services, privatization and also the role of state with regards to equity in health care which were explored further in this article. Inequitable health services in terms of access, quality and resource allocation between urban and rural population were major equity issues especially in developing countries. Other than that, issues on equity influences the choice a country makes with regards to their health financing system. Among the sources of health financing are from either taxation, out-of-pocket, social or private health insurances. In utilization of health care services, equity should analyze the actual utilization of health care and inequalities between groups for different needs and different demand curves. As for privatizing health care services, there is risk of replacement of service ethic with profit motive, resulting in inequitable access and more barriers to health care for the poor and those in rural areas. It is undeniable that health care systems have greatly transformed in many countries over the last decades; which results in many roles that should be played by the state if the objective of equity is to be achieved.